Circadian profiling reveals higher histamine plasma levels and lower diamine oxidase serum activities in 24% of patients with suspected histamine intolerance compared to food allergy and controls. Issue 4 (15th December 2017) - Pinzer, T. C.; Tietz, E.; Waldmann, E.; Schink, M.; Neurath, M. F.; Zopf, Y.
Abstract: Background: Histamine intolerance is thought to trigger manifold clinical symptoms after ingesting histamine‐rich food due to reduced activity of diamine oxidase (DAO). No study has hitherto systematically assessed daily fluctuations of histamine levels and DAO activities in symptomatic patients. The aim of the study was to investigate the presence of histamine intolerance, to therefore establish day profiles of histamine levels and DAO activities, and to compare the results between patients with suspected histamine intolerance, food allergy and healthy controls. Methods: We determined day profiles of histamine plasma levels and DAO serum activities in 33 patients with suspected histamine intolerance, in 21 patients with proven food allergy and in 10 healthy control patients. Clinical symptoms, food intolerances and further clinical and laboratory chemical parameters were evaluated. Results: Twenty‐four percent (8 of 33) suspected histamine‐intolerant patients showed elevated histamine levels during the day. That might be caused by constantly and significantly reduced DAO activities in these patients compared to food‐allergic and control patients. The remaining 25 patients presented normal histamine levels and DAO activities, but an increased prevalence of multiple food intolerances compared to the other subgroup of suspected histamine‐intolerants. There was no correlation between subjective complaints and serological histamine parameters in patients with suspected histamine intolerance. Conclusions: We determined by daily profiling that decreased DAO activities correlated with elevated histamine levels in a subgroup of suspected histamine‐intolerants. This finding discriminates these patients from food intolerant individuals with similar clinical symptoms and strongly suggests the presence of histamine intolerance.